2009
DOI: 10.1515/ijamh.2009.21.1.79
|View full text |Cite
|
Sign up to set email alerts
|

The association between oseltamivir use and adverse neuropsychiatric outcomes among TRICARE beneficiaries, ages 1 through 21 years diagnosed with influenza

Abstract: Our retrospective study found no evidence that oseltamivir treatment for influenza increased the risk of adverse neuropsychiatric outcomes among the study population. An additional study focusing on prospective medical surveillance of influenza patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Although thought initially to be oseltamivir related, the acute psychiatric reactions are probably influenza related, 36 with limited data suggesting a protective effect in oseltamivir-treated influenza patients. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Although thought initially to be oseltamivir related, the acute psychiatric reactions are probably influenza related, 36 with limited data suggesting a protective effect in oseltamivir-treated influenza patients. 38 …”
Section: Discussionmentioning
confidence: 99%
“…85 Further US healthcare database analyses have been published since the Roche review and confirm these observations in both the general population aged ≥ 1 year 86 and those aged 1–17 years 86 and 1–21 years. 87 A literature review revealed that NPAEs have been reported in Japanese and Taiwanese children with influenza before initiation of oseltamivir treatment; events occurring before treatment were similar to those occurring afterwards. 85 A similar observation was also made in a more recent Taiwanese clinical case series.…”
Section: Safetymentioning
confidence: 99%
“…The 2009 H1N1 viruses analysed, to date, are all resistant to the adamantadine class of antivirals but remain sensitive to neuraminidase inhibitors [3]. Available data indicate that the rate of prescribing antivirals to seasonal influenza virus-infected individuals, ranging in age from infants to adults, is similar between males and females in the USA [113-115]. In contrast, inappropriate prescription of antibiotics for seasonal influenza is greater for women [114].…”
Section: H1n1 Overviewmentioning
confidence: 99%